2014
DOI: 10.1111/jpi.12168
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin normalizes clinical and biochemical parameters of mild inflammation in diet‐induced metabolic syndrome in rats

Abstract: The objective of this study was to evaluate the efficacy of melatonin to affect mild inflammation in the metabolic syndrome (MS) induced by a high-fat diet in rats. Adult Wistar male rats were divided into four groups (n = 16/group): (i) control diet (3% fat); (ii) high-fat (35%) diet; (iii) high-fat diet + melatonin; and (iv) melatonin. Rats had free access to high-fat or control chow and one of the following drinking solutions for 10 wk: (a) tap water; (b) 25 μg/mL of melatonin. Plasma interleukin (IL)-1β, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 42 publications
5
61
0
2
Order By: Relevance
“…The same was observed by us in a recent study evaluating the efficacy of melatonin to affect mild inflammation in the metabolic syndrome induced by a high-fat diet in rats [31]. Although this may imply that the main effect of melatonin on body weight is exerted peripherally through a rise in the energy expenditure, the possibility of central changes in feeding regulatory mechanisms remains open.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations
“…The same was observed by us in a recent study evaluating the efficacy of melatonin to affect mild inflammation in the metabolic syndrome induced by a high-fat diet in rats [31]. Although this may imply that the main effect of melatonin on body weight is exerted peripherally through a rise in the energy expenditure, the possibility of central changes in feeding regulatory mechanisms remains open.…”
Section: Introductionmentioning
confidence: 50%
“…Although this may imply that the main effect of melatonin on body weight is exerted peripherally through a rise in the energy expenditure, the possibility of central changes in feeding regulatory mechanisms remains open. We hereby report the results of gene expression of NPY, leptin-R, POMC, prolactinreleasing peptide (PrRP), insulin-R, insulin-R substrate (IRS)-1 and IRS-2 in the medial basal hypothalamus (MBH) of the same animals employed in our previous study [31]. The changes observed were correlated with those in blood levels of leptin and adiponectin.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…We observed that mice with HFD-induced MetS had high plasmatic levels of uric acid that significantly decreased with orange juice and orange beverage, but not with alcohol intake. Thus, we propose that the uric acid decrease is due to bioactive compounds found in both orange juice and orange beverage, particularly naringenin (Wang et al, 2012) and melatonin (Cano Barquilla et al, 2014). Regarding the antioxidant enzyme activities, CAT, SOD, GPx and GR levels did not present significant changes after orange juice, orange beverage or aqueous alcoholic solution intake (Table 4).…”
Section: Effects Of Oj Ob and As Intake On Body And Visceral Weightsmentioning
confidence: 86%